2021
DOI: 10.1088/1755-1315/921/1/012030
|View full text |Cite
|
Sign up to set email alerts
|

Economic Feasibility of a Small-Scale Wind Turbine in Coastal Area of South Sulawesi

Abstract: To evaluate the exploitation potential of wind energy in the coastal area of South Sulawesi, Indonesia, an investigation on the economic feasibility of this project was performed. A 300-watt horizontal wind turbine was used as an example installed turbine. The wind speed range of 4-7 m/s which was the wind speed data in the coastal area of South Sulawesi was computed. The main economic analysis method employed was Capital Budgeting Analysis (CBA) method. In this method, 4 (four) indicators were used to evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Ozgener [20] 2010 Turkey Izmir Greenhouse * * * * SS-HAWT Off-grid Mahmuddin et al [21] 2021 Indonesia South Sulawesi -* SS-HAWT -Abdelrahim et al [22] 2022 Malaysia Malacca High-rise Building * * SS-HAWT Off-grid Rahimi and Thaghafi [23] 2006 Iran Borujerd Commercial Building * SS-HAWT On-grid Shahbazi et al [24] 2017 Iran Robat Karim Greenhouse * * SS-HAWT Off-grid Mehrani et al [25] 2014 Iran Isfahan Residential complex * VAWT (Savonius) -Kouravand [26] 2018 Iran Marvast Household * VAWT (hybrid Savonius-Darrieus) configurations from an economic perspective. The total cost (C tot ) is the sum of all component costs over the system lifetime.…”
Section: Economic Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Ozgener [20] 2010 Turkey Izmir Greenhouse * * * * SS-HAWT Off-grid Mahmuddin et al [21] 2021 Indonesia South Sulawesi -* SS-HAWT -Abdelrahim et al [22] 2022 Malaysia Malacca High-rise Building * * SS-HAWT Off-grid Rahimi and Thaghafi [23] 2006 Iran Borujerd Commercial Building * SS-HAWT On-grid Shahbazi et al [24] 2017 Iran Robat Karim Greenhouse * * SS-HAWT Off-grid Mehrani et al [25] 2014 Iran Isfahan Residential complex * VAWT (Savonius) -Kouravand [26] 2018 Iran Marvast Household * VAWT (hybrid Savonius-Darrieus) configurations from an economic perspective. The total cost (C tot ) is the sum of all component costs over the system lifetime.…”
Section: Economic Analysismentioning
confidence: 99%
“…He concluded that the WT alone can provide 3.1% of the total annual electricity consumption of the greenhouse (3568 kWh) or 12.5% of the total annual electricity consumption of the secondary water pumping, brine pumping, and fan coil (892 kWh). Mahmuddin et al [21] employed the Capital Budgeting Analysis method for a 300-watt HAWT in the South Sulawesi coastal area, Indonesia, and determined the project is not feasible for wind speed below 7 m/s. Abdelrahim et al [22] examined and optimized wind-driven charging stations for electric vehicles in high-rise buildings in Malacca, Malaysia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation